Consideration of Rocking Wind Turbine Foundations on Undrained Clay with an Efficient Constitutive Model - Behrouz Badrkhani Ajaei; Mohamed Hesham El Naggar (Applied Sciences)
The concept of rocking foundations has been successfully tested and promoted for building and bridge foundations. In this paper, the applicability of rocking foundations to wind turbines is investigated, specifically for wind turbines constructed on undrained clay. An efficient form of von Mises constitutive model with non-linear kinematic hardening is integrated with the ABAQUS finite element software by a computer code and validated against experimental data. A cohesive contact of foundation–soil with limited tension is applied to simulate suction stresses at the foundation bottom–soil interface, which better represented the rocking foundation behavior. The obtained finite element results demonstrate that by allowing minimal foundation uplift under operational loads, an existing foundation can be used to support loads from a larger wind turbine than it is designed for. Allowing such uplifts corresponds to a rocking foundation design that is demonstrated in this paper to be safe and functional for a wind turbine under both operational and extreme conditions.